Investigation on the influence of inherent AAEMs on gasification reactivity of solid digestate char. (1st March 2023) - Quan, Cui; Zhang, Jin; Tang, Zimou; Magdziarz, Aneta; Wu, Chunfei; Gao, Ningbo
Highlights: The difference in gasification reactivity of digested solid char with and without AAEMs was systematically clarified. The inherent AAEMs have promoting effect on gasification reactivity of char. The Ea value of the char after pickling increased 115.76 kJ·mol −1 . The maximum instantaneous CO concentration after char pickling was reduced by a factor of about three. Abstract: Char reactivity usually determines the overall efficiency of the entire gasification process, while the presence of the alkali and alkaline earth metals (AAEMs) has a catalytic effect on char gasification. In this study, the influence of inherent AAEMs in the gasification behaviour of char was investigated. The char sample was prepared through the pyrolysis of solid digestate derived from anaerobic co-digestion of silage and dairy cattle slurry. The raw char and HCl-washed char were characterized by elemental analyzer, ICP-OES, SEM and XRD to explore their structural changes. HCl-char loses weight in the temperature range of 440–620 °C, and the weight loss percentage is significantly higher than that of char. Ash content of char is reduced by half after a pickling process. AAEMs are largely removed after char acid pickling, resulting in an increase in activation energy of the gasification reaction and a decrease in gasification reactivity, resulting in the gasification reaction time of HCl-char longer than char. Water-soluble AAEM and ion-exchange AAEM affect the evolution of carbon structure, which directly lead to char reactivity during the gasification reaction. As the carbon is consumed, the carbon microcrystalline structure of the residual carbon tends to be ordered, resulting in fewer active free carbon sites for the gasification reaction. Kinetic analysis showed that the loss and deactivation of AAEMs after char acid washing increased the average activation energy Ea by 115.76 KJ/mol compared with the original char.